2010
DOI: 10.3109/10428191003793374
|View full text |Cite
|
Sign up to set email alerts
|

Clonal evolution in patients with chronic lymphocytic leukemia

Abstract: Newly acquired genomic abnormalities can arise during the natural history of chronic lymphocytic leukemia (CLL). Reported frequencies range from 17 to 42%, based on several series with small numbers of patients (n ¼ 31-64) and with a limited follow-up (60-83 months) [1][2][3][4]. It has been shown that this complication appears more frequently in patients with unmutated IGVH (immunoglobulin heavy chain variable region) and after treatment. Deletion (del) of 17p13 is unusual as clonal evolution (CE) in untreate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
14
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 8 publications
1
14
1
Order By: Relevance
“…New high-risk genomic aberrations (11q22 and 17p13 deletion) occurred, respectively, in 8%, 9.4%, 8.2%, 16%, and 5.7% of patients (15)(16)(17)(18)(19). The high percentage of highrisk aberrations in the Loscertales paper can probably be explained by the fact that all patients had progressive disease at second FISH analysis (18). In our study, none of the patients acquired a trisomy 12.…”
Section: Discussionsupporting
confidence: 39%
See 4 more Smart Citations
“…New high-risk genomic aberrations (11q22 and 17p13 deletion) occurred, respectively, in 8%, 9.4%, 8.2%, 16%, and 5.7% of patients (15)(16)(17)(18)(19). The high percentage of highrisk aberrations in the Loscertales paper can probably be explained by the fact that all patients had progressive disease at second FISH analysis (18). In our study, none of the patients acquired a trisomy 12.…”
Section: Discussionsupporting
confidence: 39%
“…This study showed CE after a median interval between the two sequential FISH analyses of 40 m with a median follow-up after diagnosis of 89 m. Shanafelt et al (15) observed only one case of CE in 71 patients (1.4%) who got a sequential FISH 2 yr after the baseline analysis, but 17 of 63 patients (23%) showed CE in samples investigated more than 5 yr apart. Median time to CE in the other published series varied between 30 and 64 m (16)(17)(18)(19).…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations